On the hellebore trail: an anthropological research into madness - Maieron, Mario Augusto (Medicina Historica, 2018)
Beginning with myth, this article retraces the history of an antique psychiatric therapy, hellebore, present in medicine from Hippocratic times until well beyond the age of Enlightenment.Providing a background are aspects of the anthropological history of madness, relating to culture, not only medical, together with literary examples, which were reiterated from classic antiquity up to ‘900.